Warehouse Door Security System Based on Internet of Things (IoT) Using Reed Switch Sensor Connected to Smartphone Notification - Gunawan, Gugun; Utami, Alia Tri; Sudrajat, Asep; Irawan, Debi (Informatics Management, Engineering and Information System Journal, 2024)
A robust warehouse door security system is crucial for safeguarding assets and stored objects against theft or illegal access. This research seeks to build and construct an Internet of Things (IoT)-based security system employing reed switch and PIR sensors to identify suspicious behavior near the warehouse entrance. Developed for PT. Anugerah Terang Persada's system incorporates real-time notifications for the warehouse proprietor or manager's smartphones. Reed switch sensors identify the door's opening and closing, whereas PIR sensors observe movement in the surrounding area. The ESP32-CAM microcontroller processes data from various sensors, capturing photos or movies during unforeseen movements or door opens. This data is transmitted via the internet to the mobile application, facilitating real-time notifications. The principal advantage of this research is improved warehouse security using accessible and cost-effective IoT technology. The solution delivers enhanced efficiency relative to conventional security approaches by providing instantaneous alerts and visual proof for prompt action. The ESP32-CAM facilitates automatically recording photos or videos upon detecting suspicious activity, thereby enhancing security by preserving digital evidence for further review. This system can also be linked with other IoT devices, improving overall security monitoring. This research presents novel options for firms requiring dependable and economical warehouse security, diminishing dependence on conventional ways while enhancing flexibility and convenience in facility administration.